Class Altruism and Redistribution. Issue 640 (22nd March 2021) - Ghiglino, Christian; Juárez-Luna, David; Müller, Andreas
Abstract: Why do tax rates vary so much across countries? We study the role of other-regarding preferences and ethnic fragmentation in redistribution. A government is elected by altruistic voters and chooses a redistributive income tax. Altruism is directed towards social identity groups. Three main factors yield low levels of redistribution: (i) strong in-group altruism among rich voters—referred to as class altruism; (ii) weak universal altruism—in particular among the rich; and (iii) ethnic fragmentation among poor voters. We document survey evidence that the pattern of altruism in the United States and the European Union is consistent with the observed differences in taxes.